Recruitment strategies of methamphetamine-using men who have sex with men into an online survey. (February 2015) - Wilkerson, J. Michael; Shenk, Jared E.; Grey, Jeremy A.; Rosser, B. R. Simon; Noor, Syed W.
Abstract Recruiting hidden populations into online research remains challenging. In this manuscript, we report lessons learned from our efforts to recruit methamphetamine-using men who have sex with men. Between July and October 2012, we implemented a four-phase recruitment strategy to enroll a total of 343 methamphetamine-using MSM into an online survey about recent substance use, sexual behavior, and various psychosocial measures. The four phases were implemented sequentially. During phase one, we placed advertisements on mobile applications, and during phase two, we placed advertisements on traditional websites formatted for browsers. During phase three, we used e-mail to initiate snowball recruitment, and during phase four, we used social media for snowball recruitment. Advertisements on mobile devices and websites formatted for browsers proved to be expensive options and resulted in few eligible participants. Our attempts to initiate a snowball through e-mail also proved unsuccessful. The majority (n = 320) of observations in our final dataset came from our use of social media. However, participant fraud was a concern, requiring us to implement a strong participant verification protocol. For maximum recruitment and cost-effectiveness, researchers should use social media for recruitment provided they employ strong participant verification protocols.